Histone Demethylase UTX and Chromatin Remodeler BRM Bind Directly to CBP and Modulate Acetylation of Histone H3 Lysine 27. - Tie, F.; Banerjee, R.; Conrad, P.A.; Scacheri, P.C.; Harte, P.J. (Molecular and Cellular Biology, 2012)
Trithorax group (TrxG) proteins antagonize Polycomb silencing and are required for maintenance of transcriptionally active states. We previously showed that the Drosophila melanogaster acetyltransferase CREB-binding protein (CBP) acetylates histone H3 lysine 27 (H3K27ac), thereby directly blocking its trimethylation (H3K27me3) by Polycomb repressive complex 2 (PRC2) in Polycomb target genes. Here, we show that H3K27ac levels also depend on other TrxG proteins, including the histone H3K27-specific demethylase UTX and the chromatin-remodeling ATPase Brahma (BRM). We show that UTX and BRM are physically associated with CBP in vivo and that UTX, BRM, and CBP colocalize genome-wide on Polycomb response elements (PREs) and on many active Polycomb target genes marked by H3K27ac. UTX and BRM bind directly to conserved zinc fingers of CBP, suggesting that their individual activities are functionally coupled in vivo. The bromodomain-containing C terminus of BRM binds to the CBP PHD finger, enhances PHD binding to histone H3, and enhances in vitro acetylation of H3K27 by recombinant CBP. brm mutations and knockdown of UTX by RNA interference (RNAi) reduce H3K27ac levels and increase H3K27me3 levels. We propose that direct binding of UTX and BRM to CBP and their modulation of H3K27ac play an important role in antagonizing Polycomb silencing.